Mandapa of the Hazareshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The Hazareshwar Temple is constructed in the trabeate style, which is most evident in its ceiling design. The pillars and pilasters of the mandapa (pillared hall) support four lintels, forming a large square with concentric squares. Each square features a kirtimukha (face of glory) at its corners, and at the centre of the ceiling, there is a beautifully carved lotus bloom.